BIOCHEMICAL CHANGES IN THE BLOOD OF CLARIAS GARIEPINUS JUVENILES FED WITH POULTRY WASTE (American International Journal of Biology and Life Sciences, 2023)
Artificial Nutrition is one of the most important means of boosting production in fish farming and maximizing the cost of feeding, effectively increasing profitability in fish production. This study evaluates the effect of poultry waste meal on the serum, kidney and liver of Clarias gariepinus. After acclimatization, the fish samples were grouped into groups 1, G1, fed with poultry waste and group 2, G2, with Coppens feed. The result showed a significantly higher difference (P > 0.05) in the mean serum composition for Fish fed with poultry waste for Aspartate Amino Transferase, A.S.T. (69.50±1.05), Alanine Amino Transferase, A.L.T. (69.95±1.07), Alkaline Phosphate, A.L.P. (69.10±1.31) compared to that of those fed with Coppens feed A.S.T. (54.87±1.47); A.L.T. (59.67±1.53); A.L.P. (56.47±0.50) respectively. High-density lipoprotein, HDL was significantly (P > 0.05) higher in C. gariepinus juveniles fed with poultry Coppens (71.07±1.17) than those provided with poultry waste (63.13±0.93). Alternately, Low-density lipoprotein, LDL, was significantly higher (P > 0.05) in Fish fed with poultry waste (81.33±0.93) than those provided with Coppens (74.17±1.08). Triglyceride was considerably higher in C. gariepinus juveniles fed with poultry waste (81.33±0.93) than in C. gariepinus juveniles fed with Coppens (74.17±1.08). The composition of Total Cholesterol in both experimental Fish is 86.6±0.60 for C. gariepinus juveniles fed with Coppens and 94.27±1.62 for C. gariepinus juveniles fed with poultry waste. The mean biochemical composition of the liver of C. gariepinus juvenile fed poultry waste showed a  higher significant difference (P > 0.05) for A.S.T. (75.77±0.72), A.L.T. (60.17±0.12), A.L.P. (61.40±1.48), LDL (77.03±1.21), Triglyceride (77.03±0.93) and Total Cholesterol (68.87±0.46) than those fed with Coppens feed although HDL (78.00±1.14) was significantly higher in those provided with Coppens than those fed with poultry waste (59.73 ±1.07) while for the kidney A.S.T. (51.27±1.08), A.L.T. (47.77±0.87), A.L.P. (69.10±1.31), LDL (81.33±0.93) and Triglyceride (70.30±1.25) had a significantly higher difference (P > 0.05) than that C. gariepinus fed poultry waste A.S.T. (46.20±0.35), A.L.T. (39.33±1.15), A.L.P. (43.03±11.58), LDL (74.17±1.08) and Triglyceride (67.83±1.19) except HDL (71.07±1.17) which was significantly higher in Coppens fed Fish than those provided with poultry waste (63..13±0.93). An increase in biochemical composition observed in this study suggests a disruption in the metabolism of the fish juveniles fed with poultry waste. Therefore, poultry waste should not be depended on solely as fish feed for Clarias gariepinus.JEL Classification Codes: L65, Q53.